A condition called love. 7 - Morino, Megumi (Kodansha USA Publishing, LLC, 2024)
"Hotaru and Hananoi-kun have been together for nearly half a year now, and the first summer break of their relationship is right around the corner! Hotaru decides to make herself as attractive as possible--both inside and out--in order to be a good girlfriend to Hananoi-kun. Meanwhile, an all-new romance seems to be budding in their friend group."--